THE EFFECT OF USING SCROL STRATEGY TOWARD STUDENTS’ READING COMPREHENSION ON HORTATORY EXPOSITION TEXT AT THE ELEVENTH GRADE OF SMAN 1 CANDUANG - Putri Helmina; Melyann Melani (English Language Teaching and Research, 2017)
This research was aimed at identifying the effect of using SCROL (Survey, Connection, read, Outline, Look Back) strategy toward students’ reading comprehension on hortatory exposition text. Since hortatory exposition is a type of text that influence reader to do something or act in certain way, a profound understanding of the text is something that the students should possessed. SCROL provides procedures that help students to achieve good comprehension. This researcher used a quasi-experimental design by using the pretest-posttest control group design with purposive sampling technique. The pre-test and post-test scores of the experiment class, indicate that the t-obtained (5.44) is higher than the t-table (1.68488) with degree of freedom (df) = 39 and (α) = 0.05. Therefore, alternative hypothesis (Ha) is accepted and it means that there is significant effect of SCROL strategy toward the students’ reading comprehension on hortatory exposition text. The calculation of post-test both classes indicated that the t-o is (2.82) which is higher than the t-table (2, 02439), with degree of freedom 20 + 20 – 2 = 39 and (α) = 0,025. Thus, the alternative hypothesis (Ha) was accepted and it means that there is significant difference between using SCROL strategy and common strategy. Finally, t-obtained both of classes is (2.82) which is higher than t-table (1.68488) with (α) = 0. 05. Therefore, the alternative hypothesis (Ha) is accepted and it means that SCROL strategy is better than common strategy in teaching reading comprehension on hortatory exposition text. Key Words: SCROL Strategy, Reading Comprehension, Hortatory Exposition